Hormone replacement therapy and cervical cancer: a systematic review of the literature. (4th March 2021) - Vargiu, V.; Amar, I. D.; Rosati, A.; Dinoi, G.; Turco, L. C.; Capozzi, V. A.; Scambia, G.; Villa, P.
Abstract: Gynecological tumor treatment, including cervical cancer (CC) treatment, often leads to iatrogenic premature menopause. This highlights the critical importance of investigating indications for hormone replacement therapy (HRT), as most patients, thanks to the improvement in diagnosis and treatment, have to deal with the sequelae of their cancer treatments for many years. This systematic review aims to provide an overview of the current knowledge regarding the risks of HRT and CC. In particular, we aim to investigate whether the use of HRT can increase CC incidence, and evaluate its risk in CC survivors. A systematic review, in agreement with PRISMA guidelines, of the English literature present in PubMed and SCOPUS has been performed. A total of 2805 articles have been screened, of which 10 were considered eligible. Several studies reported a significantly reduced risk of developing cervical squamous cell carcinoma in postmenopausal women treated with HRT, while a weak increase in the incidence of adenocarcinoma has been shown. No evidence reports a harmful effect of HRT on CC oncological outcome, while several benefits, in terms of reduced metabolic risk and increased quality of life, have been described, thus concluding that HRT should be offered to young CC survivors for the management of early menopause.